Any Link Between Legal Central Bank Independence and Inflation? : Evidence from Latin America and the Caribbean - Jacome, Luis (IMF Working Papers; Working Paper, 2005)
This paper reviews central bank legislation in 24 countries in Latin America and the Caribbean during the 1990s. Using panel regressions, we find a negative relationship between legal central bank independence (CBI) and inflation. This result holds for three alternative measures of CBI and after controlling for international inflation, banking crises, and exchange regimes. The result is also robust to the inclusion of a broader indicator of structural reforms that usually go along with changes in central bank legislation, illustrating the complementary nature of various aspects of economic reform. The paper fails, however, to find a causal relationship running from CBI to inflation.